PROGNOSTIC SIGNIFICANCE OF VEGFA AND IL6 GENE POLYMORPHISM IN DIABETIC FOOT SYNDROME (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Diabetes mellitus is one of the serious medical and social problems of the modern world. Diabetic foot syndrome is one of the terrible complications of diabetes mellitus. In 55% of cases, this complication occurs in patients aged 25 to 75 years. To implement the basic principles of modern personalized medicine, it is relevant to study the genetic aspect of multifactorial diseases. The aim of the study was to analyze the correlation between the G634C polymorphisms of the VEGFA gene and the C174G polymorphisms of the IL6 gene and the development of diabetic foot syndrome in patients with diabetes mellitus. The clinical group included 96 patients aged 40 to 75 years with diabetes mellitus complicated by diabetic foot syndrome. The control group consisted of 83 healthy individuals. The results obtained by the authors demonstrate that the presence of the G/G genotype of the G634C polymorphism of the VEGFA gene, as well as the C/G genotype of the C174G polymorphism of the IL6 gene, has a clear correlation with predisposition to the development of diabetic foot syndrome. Carrying the G/G genotype of the G634C polymorphism of the VEGFA gene and the C/C genotype of the C174G polymorphism of the IL6 gene is associated with a protective effect on the development of diabetic foot syndrome.